Diversity of Vachellia nilotica rhizosphere bacteria in the savanna of Baluran National Park, Indonesia and their potential for hydrolytic enzyme production - NI’MATUZAHROH NI’MATUZAHROH; MOCH. AFFANDI; RICO RAMADHAN; FATIMAH FATIMAH; AGUS SUPRIYANTO; SALAMUN SALAMUN; TRI NURHARIYATI; ALMANDO GERALDI; JUNAIRIAH JUNAIRIAH; JOHAN SETIAWAN; BRIGITA NUR DIYAN AGUSTIANA; ARSY HABI PRIYATAMA; KIRANA ATMANINDYA; DELA DWI ALAWIYAH; ELVIS PERDANA PUTRA; ANA MARIATUL KHIFTIYAH; SILVIA KURNIA SARI; CHRISTOPHER CLEMENT (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ni’matuzahroh, Affandi M, Ramadhan R, Fatimah, Supriyanto A, Salamun, Nurhariyati T, Geraldi A, Junairiah, Setiawan J, Agustiana BND, Priyatama AH, Atmanindya K, Alawiyah DD, Putra EP, Khiftiyah AM, Sari SK, Clement C. 2025. Diversity of Vachellia nilotica rhizosphere bacteria in the savanna of Baluran National Park, Indonesia and their potential for hydrolytic enzyme production. Biodiversitas 26: 1754-1767. Vachellia nilotica, a leguminous plant introduced to Baluran National Park as a firebreak, is now causing environmental problems due to its invasiveness, which hinders the growth of native plants. Despite significant ecological changes, there is no data regarding the impact of this plant invasion on soil microorganisms. This study aimed to assess the bacterial diversity in the rhizosphere of V. nilotica and investigate the bacteria's ability to produce hydrolytic enzymes. The bacterial community was identified using Next-Generation Sequencing (NGS), and a conventional isolation technique. A total of 99,520 Operational Taxonomic Units (OTUs) were obtained, encompassing a rich diversity of 4,631 species. These species belonged to four phyla (i) Pseudomonadota; (ii) Actinomycetota; (iii) Bacillota; and (iv) Acidobacteriota. Additionally, 26 isolates were obtained through conventional isolation, and all of them can produce hydrolytic enzymes, including protease, lipase, amylase and cellulase. A total of 9 isolates showed highest proficiency in producing hydrolytic enzymes, of which 8 belonged to the Bacillota phylum and 1 isolate showed similar characteristic with Acidobacteriota phylum. The isolates SAV 2.NA.1.5.6 and SAV 2.NA.2.4.3 exhibited multiple enzyme activities and were classified as Bacillota. The findings indicate that the rhizosphere of V. nilotica contains a high diversity of bacteria, including those capable of producing hydrolytic enzymes. This information can serve as a foundation for managing V. nilotica and promoting sustainable development by leveraging the potential of rhizosphere bacteria in this plant. To our knowledge, no prior research has been conducted on this topic in the savanna area of BNP.